Competitive binding of quinone and antibiotic stigmatellin to reaction centers of photosynthetic bacteria - Gerencsér, László (Acta Biologica Szegediensis, 2004)
Stigmatellin bound to the QB site of the reaction center of photosynthetic bacteria is one of the most potent inhibitors of interquinone electron transfer. In addition to its inhibitory effect, it can be used to model protonated semiquinone and to probe the electrostatic environment. These properties were studied by two independent methods in isolated reaction centers and in chromatophores from cytochrome c-less mutant of Rhodobacter sphaeroides. The binding of the stigmatellin was detected by photochemical assay (flash-induced charge recombination of the reaction center) and the protonation/deprotonation equilibrium of the phenolic group by spectral assay monitoring the band peaks at 272 nm and 340 nm of the absorption spectra of the stigmatellin (Δe272(deprot/prot) = 10 mM-1·cm-1). The dissociation constant of stigmatellin binding increased by about two orders of magnitude from 4 nM (pH 8.5) to 350 nM (pH 11.0) in chromatophores indicating the difference in binding affinities between the protonated and deprotonated forms of the stigmatellin. The observed pK of the phenolic proton has proved to be very sensitive to the surroundings: 9.4 (in aqueous solution), 9.4-10.3 (in different detergents) and 10.2 (in excess to RC in detergent n-octyl-b-D-glycopyranoside). This wide range of values may indicate highly different electric fields (energetic coupling with the phenolic proton of the stigmatellin) and/or solvation energy of stigmatellin in different phases of the detergent/protein/membrane system.